Fundamentals of corporate finance - Ross, Stephen A.; Westerfield, Randolph W.; Jordan, Bradford D. (Chicago : Irwin, 1995)
Business
Keywords: Corporate finance; Financial planning; Capital budgeting; Capital market; Financial policy; Capital structure; Dividends; Cash management; Credit management